Pengembangan Sumberdaya Pegawai Dalam Administrasi Kependudukan di Dinas Kependudukan Dan Pencatatan Sipil Kota Manado - Chuanda, Pricilia; Kaunang, Markus; Londa, Very Y (JURNAL ILMIAH SOCIETY, 2016)
This research aims to analyze the human resources development In Population Administration Field At Population and Civil Registration Offie at Manado. Research method is qualitative method. The research found that employee development through education and training have not been fully formed attitude, knowledge and skill of employee’s work in Population Administration Field at Population And Civil Registration Office. This is because the education and training activities which be done in form of education and formal training, rule of law socialization, and general technical guidance of implementation rule of law, and in the implementation more often be coordinated with Staffing Agency and Region Training, subpart of Population And Civil Registration In Government section and Public Relation and Indonesia Ministry of Internal Affairs Keyword : Resources, Training, Education